2009
DOI: 10.1063/1.3211311
|View full text |Cite
|
Sign up to set email alerts
|

Formation of periodic strained layers associated with nanovoids inside a silicon carbide single crystal induced by femtosecond laser irradiation

Abstract: We observed the formation of subwavelength periodic strained layers associated with nanovoids in the cross section of femtosecond laser-irradiated lines written inside 4H-SiC single crystals. Both conventional and high-voltage transmission electron microscopies were carried out for microstructural analyses. The cross section of the irradiated lines consists of four to six groups of fine periodic structures. Each group is composed of strained layers with a typical spacing of 150 or 300 nm. The layers extend alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 12 publications
3
44
1
Order By: Relevance
“…g and h). Another group has also observed that the formation of periodic strained layers associated with nanovoids inside a SiC single crystal . Since a SiC is an indirect band gap semiconductor, their results are consistent with our interpretation that the nanostructures can be formed inside a material only if it is an indirect bandgap semiconductor.…”
Section: Methodssupporting
confidence: 90%
“…g and h). Another group has also observed that the formation of periodic strained layers associated with nanovoids inside a SiC single crystal . Since a SiC is an indirect band gap semiconductor, their results are consistent with our interpretation that the nanostructures can be formed inside a material only if it is an indirect bandgap semiconductor.…”
Section: Methodssupporting
confidence: 90%
“…in good agreement with experimental results[4]. (The value s k depends on excess nonequilibrium electrons concentration on the critical one and on refractive index of semiconductor.)…”
supporting
confidence: 76%
“…Back wave, that go toward the laser radiation and is needed for interference, is created due to reflection by system of formed temporary and remnant regular nanostructures. Since plasma channel is surrounded by semiconductor matter, the period of resulting nanostructures is In experiments [4] the array of laser beam multifilamentation was observed along laser beam track in semiconducting 4H-SiC due to excess laser beam intensity, see fig.1a,b, similar as for gases [12] and dielectrics [13]. The later nonlinear effect includes the process of nonequilibrium solidstate plasma formation..…”
mentioning
confidence: 97%
See 2 more Smart Citations